ANALYSIS ATTITUDE BRIDES AND GROOMS TO BE TOWARD PREMARITAL HIV TESTING - Linda Dewanti; Visky Afrina; Budi Prasetyo (UNIVERSITAS AIRLANGGA, 2022)
Background: In Surabaya, every bride and groom to be is required to do a premarital HIV testing, to knows their HIV status is positive or negative. In 2018, there were 127 HIV positive cases in bride and groom to be, but only 7.8% canceled marriage while 40.9% continued marriage, even 51.3% had unknown information. This study aims to analyze the attitude and knowledge of the bride and groom regarding premarital HIV testing. Method: this research was conducted at the Putat Jaya Health Center in Surabaya in July 2020 – January 2021, this type of research was a quantitative analytic design with a cross sectional research design. The number of samples was 72 prospective brides consisting of 36 prospective brides and 36 prospective grooms. The sampling technique used purposive sampling. The variables used were the attitude and knowledge of the bride and groom about premarital HIV testing. The instrument used was a questionnaire that had previously been tested for validity by the researcher. Data analysis used the chi-square test and fisher's exact test. Results: Overall the bride and groom who have good knowledge will tell their partner about the results of the HIV positive test they got, besides that 42.3% of the brides who are less knowledgeable are not willing to carry out routine consultations and treatment, but a small proportion are also found (18.8 %) of prospective brides and grooms who have good knowledge but not willing to carry out routine consultations and treatment if they get HIV positive Conclusion: in general, the knowledge of the prospective bride and groom about HIV will influence the prospective bride and groom in their attitude, being willing to tell their HIV positive results to their partners or being willing to carry out continuity care for treatment, but not always good knowledge will give the prospective bride a positive attitude , so this needs more handling from health workers, especially in communication and education. Key words: attitudes, knowledge , premarital HIV testing